Mapping research trends in mathematical creativity in mathematical instructional practices: A bibliometric analysis - Abdul Aziz Saefudin; Ariyadi Wijaya; Siti Irene Astuti Dwiningrum (Journal of Pedagogical Research, 2023)
Mathematical creativity is among the most intriguing research fields in the world. This is plausible because research on mathematical creativity, particularly in the field of education, has a positive impact on many dimensions of life. Even though numerous studies have been conducted on this topic, there are still many aspects that have not been examined. Using bibliometric analysis, the authors of this study evaluated scientific articles on mathematical creativity from 2002 to 2022 that were indexed in Scopus using Biblioshiny and VOSviewer. The authors analyzed 162 publications in terms of document distribution patterns and growth trends, contributions and impacts from countries, institutions, authors, and journals, patterns of development and evolution of the theme of mathematical creativity, and future research opportunities. Despite a decrease in the average number of citations per document, the results suggest a significant increase in the number of publications between 2002 and 2022. The United States and the University of Haifa are the nations and institutions with the highest publication output, ZDM-Mathematics Education has the highest impact, and Bicer is a core author who is extremely productive and influential. "Creativity" has been the most popular keyword over the past two decades, but it is not the only one. This study encourages future research on mathematical creativity in mathematics education to not only focus on the theme of discipline-specific instructional practices, but also on the theme of general instructional practices involving more person, process, product, and press/environment creativity.